A study of electron and thermal transport in layered titanium disulphide single crystals. (13th November 2017) - Suri, Dhavala; Siva, Vantari; Joshi, Shalikram; Senapati, Kartik; Sahoo, P K; Varma, Shikha; Patel, R S
Abstract: We present a detailed study of thermal and electrical transport behavior of single crystal titanium disulphide flakes, which belong to the two dimensional, transition metal dichalcogenide class of materials. In-plane Seebeck effect measurements revealed a typical metal-like linear temperature dependence in the range of 85–285 K. Electrical transport measurements with in-plane current geometry exhibited a nearly T 2 dependence of resistivity in the range of 42–300 K. However, transport measurements along the out-of-plane current geometry showed a transition in temperature dependence of resistivity from T 2 to T 5 beyond 200 K. Interestingly, Au ion-irradiated TiS2 samples showed a similar T 5 dependence of resistivity beyond 200 K, even in the current-in-plane geometry. Micro-Raman measurements were performed to study the phonon modes in both pristine and ion-irradiated TiS2 crystals.